A cultura local em sala de aula: o repente como elemento motivacional e identitário para as práticas de letramento - Carneiro, Maria Valmirene Oliveira (2016)
This paper presents a didactic-pedagogic proposition from a poetic-musical genre of oral literature, the repente, applied in the Portuguese language classes, with a group of sixth (6th year) of elementary school of the municipal public school in Riachão do Jacuípe in order to promote literacy, from a critical reading and appreciation of local culture and identity of students. In this proposition, the students recorded and passed to the writing mode repentes, created by a pair of jacuipenses repentistas. We discussed through these speeches and other activities proposed in the didactic sequence, how speech and writing assume a continuum of relationship, and observe the peculiar characteristics of repente genre. One of the justifications for the development of these activities in the classroom, it was sure that the Portuguese language teaching should not be guided only in written text. The interaction of the individual in society does not only happen by written communication, but also by gestures, the visual and the oral texts from a verbal interaction of social practices of the language. As a theoretical basis, we focus the discussion, especially in studies of Bakhtin (1997; 2010), Marcuschi (2007; 2008), Soares (2004; 2010), Kleiman (1995; 2000; 2005), PCN (2001), Cascudo (1994; 2010), Zumthor (1997; 2000), Azevedo (2006; 2008), Warnier (2000), Brandão (2008), Laraia (2009), Santos (1994), Hall (1997; 2008), Arantes (1998), Antunes (2003) Travaglia (2009), Garanhuns ( 2007), Goldenberg (2011), among others. By understanding the Portuguese language teaching must have the language as a starting point and arrival, orality genres come to enrich and make the most motivated and productive teaching-learning process, since the proposed activities are characterized as events the promotion of reading, listening, oral expression, textual production and enhancement of socio-cultural identity of the student, adapting them to different situations of interaction. Thus, we checked that it is possible to promote very rich learnings with the insertion of texts originating from oral culture in the Portuguese language classes.